2018
DOI: 10.1163/15685411-00003127
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and molecular characterisation of Aphelenchoides primadentus n. sp. (Nematoda: Aphelenchoididae) from northern Iran

Abstract: Aphelenchoides primadentusn. sp. is described and illustrated based on its morphological, morphometric and molecular characters. It was recovered from natural forests of northern Iran in association with mosses. The new species is characterised by its body length of 502-613μm in females and 461-564μm in males, presence of three lines in the lateral fields, a low lip region slightly offset by a shallow depression, 11.1-13.8μm long stylet in females, its conus being longer than the shaft (m = 53.0-68.5) and bear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The new species was provisionally assigned to the group 2 of intraspecies grouping of Aphelenchoides. However, this is an artificial framework (Mobasseri et al, 2018), and in some cases, the species could not easily assigned to either of those groups. In their extensive study, van Megen et al (2009) investigating a broad range of taxa using SSU rDNA sequences, concluded that the tail tip characters could support some cladogenesis events, and also correlated the tail tip characters with the resolved relations between two genera, Laimaphelenchus Fuchs, 1937 and Aphelenchoides.…”
Section: Journal Of Nematologymentioning
confidence: 99%
See 2 more Smart Citations
“…The new species was provisionally assigned to the group 2 of intraspecies grouping of Aphelenchoides. However, this is an artificial framework (Mobasseri et al, 2018), and in some cases, the species could not easily assigned to either of those groups. In their extensive study, van Megen et al (2009) investigating a broad range of taxa using SSU rDNA sequences, concluded that the tail tip characters could support some cladogenesis events, and also correlated the tail tip characters with the resolved relations between two genera, Laimaphelenchus Fuchs, 1937 and Aphelenchoides.…”
Section: Journal Of Nematologymentioning
confidence: 99%
“…The genus Aphelenchoides Fischer, 1894 (family Aphelenchoididae Skarbilovich, 1947), has around 175 nominal species (Mobasseri et al, 2018). This could also be an underestimate, and several sequences deposited at the GenBank database for example, are identified only at the genus level.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The taxonomy of aphelenchs in Iran has been recently reviewed by Mobasseri, Pourjam, and Pedram () and Aliramaji, Pourjam, Jahanshahi Afshar, Álvares‐Ortega, and Pedram (). The present study is part of a continuing survey of aphelenchs from Iran with the discovery of another new species of Basilaphelenchus from a dead tree.…”
Section: Introductionmentioning
confidence: 99%
“…Several representatives of Aphelenchoidea (Fuchs, 1937) have been reported from Iran, and currently the genera Aphelenchoides (Fischer, 1894), Aprutides (Scognamiglio et al, 1970), Basilaphelenchus (Pedram et al, 2018), Cryptaphelenchus (Fuchs, 1937), Devibursaphelenchus (Kakulia, 1967), Ektaphelenchus (Fuchs, 1937), Ektaphelenchoides (Baujard, 1984), Laimaphelenchus (Fuchs, 1937), Robustodorus (Andrássy, 2007), Seinura (Fuchs, 1931), and Sheraphelenchus (Nickle, 1970) are known that occur in the country (e.g. Pourjam and Bert, 2006 ; Pedram et al, 2011, 2012, 2018a, b ; Atighi et al., 2012a, b ; Moosavi et al, 2014 ; Miraeiz et al, 2015 ; Adeldoost et al, 2016 ; Pedram, 2017, 2019 ; Aliramaji et al., 2018, 2019, 2020 ; Mobasseri et al, 2018 ; Mirzaie Fouladvand et al, 2019a, b ). Schistonchus Cobb, 1927 occurs in the country with only one representative, the type species, Schistonchus caprifici (Gasparrini, 1864) Cobb, 1927, being reported in three conference abstracts ( Kheiri and Goldansaz, 1998 ; Pakniyat and Taghizadeh, 2000 ; Namjoo et al., 2019 ) with no morphological and morphometric data.…”
mentioning
confidence: 99%